Resilience and sustainability in the activities of a higher education institution - S. O. Serbenyuk (Law and Safety)
The activities of a higher education institution in the context of achieving the UN Sustainable Development Goals are one of the important factors in ensuring economic, social and environmental security. Being educational and research centres of local communities, universities have an important impact on their residents, and with active educational activities and cooperation, this impact increases significantly. Another extremely important factor in this growth is teaching, research, educational and advisory activities and cooperation at the regional, national and international levels.